Socio-legal systems and implementation of the Nash solution in Debreu–Hurwicz equilibrium - Haake, Claus-Jochen; Trockel, Walter (Review of Economic Design)
Abstract In this article we combine Debreu’s (Proc Natl Acad Sci 38(10):886–893, 1952) social system with Hurwicz’s (Econ Design 1(1):1–14, 1994; Am Econ Rev 98(3):577–585, 2008) ideas of embedding a “desired” game form into a “natural” game form that includes all feasible behavior, even if it is “illegal” according to the desired form. For the resulting socio-legal system we extend Debreu’s concepts of a social system and its social equilibria to a socio-legal system with its Debreu–Hurwicz equilibria. We build on a more general version of social equilibrium due to Shafer and Sonnenschein (J Math Econ 2(3):345–348, 1975) that also generalizes the dc-mechanism of Koray and Yildiz (J Econ Theory 176:479–502, 2018) which relates implementation via mechanisms with implementation via rights structures as introduced by Sertel (Designing rights: invisible hand theorems, covering and membership. Tech. rep. Mimeo, Bogazici University, 2001). In the second part we apply and illustrate these new concepts via an application in the narrow welfarist framework of two person cooperative bargaining. There we provide in a socio-legal system based on Nash’s demand game an implementation of the Nash bargaining solution in Debreu–Hurwicz equilibrium.

Educational Assimilation of First-Generation and Second-Generation Immigrants in Germany - Gries, Thomas; Redlin, Margarete; Zehra, Moonum (Journal of International Migration and Integration)
Abstract Using data from the German Socio-Economic Panel for 1984–2018, we analyze the intergenerational education mobility of immigrants in Germany by identifying the determinants of differences in educational stocks for first- and second-generation immigrants in comparison to individuals without a migration background. Our results show that on average, first-generation immigrants have fewer years of schooling than native-born Germans and have a disproportionate share of lower educational qualifications. This gap is strongly driven by age at immigration, with immigration age and education revealing a nonlinear relationship. While the gap is relatively small among individuals who migrate at a young age, integrating in the school system at secondary school age leads to large disadvantages. Examining the educational mobility of immigrants in Germany, we identify an inter-generational catch-up in education. The gap in education between immigrants and natives is reduced for the second generation. Finally, we find that country of origin differences can account for much of the education gap. While immigrants with an ethnic background closer to the German language and culture show the best education outcomes, immigrants from Turkey, Italy, and other southern European countries and especially the group of war refugees from Syria, Afghanistan, Iraq and other MENA countries, have the lowest educational attainment.

Anthropogenic climate change: the impact of the global carbon budget - Redlin, Margarete; Gries, Thomas (Theoretical and Applied Climatology)
Abstract Using time series data for the period 1959–2015, our empirical analysis examines the simultaneous effects of the individual components of the global carbon budget on temperature. Specifically, we explore the possible effects of carbon emissions caused by fossil fuel combustion, cement production, land-use change emissions, and carbon sinks (here in terms of land sink and ocean sink) on climate change. The simultaneous inclusion of carbon emissions and carbon sinks allows us to look at the coexistent and opposing effects of the individual components of the carbon budget and thus provides a holistic perspective from which to explore the relationship between the global carbon budget and global warming. The results reveal a significant positive effect of carbon emissions on temperature for both fossil fuels emissions and emissions from land-use change, confirming previous results concerning carbon dioxide and temperature. Further, while ocean sink does not seem to have a significant effect, we identify a temperature-decreasing effect for land sink.

Kollusion durch Plattformen - der Einfluss von Tank-Apps auf den Preiswettbewerb von Tankstellen in Deutschland - Heinze, Erik

Big Data in Digital Markets - Challenges for Competition Policy to Protect Consumer Welfare - Rayhan, Shahi

Network Development of Low-Cost Carriers at German Airports - Joshan, Saeid

Plattformgestaltungen auf digitalen Märkten - eine Analyse der Wohlfahrtseffekte - Ajredini, Zurkani

Marktmachtmissbrauch digitaler Plattformen - eine Analyse anhand der zehnten Novelle des GWB - Kanne, Niklas

Marktmachtmissbrauch von Google – Eine wettbewerbspolitische Analyse - Klüppel, Pascal

Preisabsprachen in der Automobilindustrie - eine wettbewerbspolitische Analyse - Yigitbas , Osman

Facebooks digitale Währung - eine wettbewerbspolitische Analyse - Schulte, Marcel

Die Aufteilung der Barentsseegebiete mithilfe des Adjusted Winner Verfahrens bei asymmetrischen Machtverhältnissen - N., N.

Versionisierung von Serviceleistungen auf Videoplattformen - N., N.

Kindergarten Allocation through Matching Mechanisms - N., N.

Faire Profitverteilung in Energienetzwerken - eine spieltheoretische Analyse von Microgrids - N., N.

"First-Party-Content" auf zweiseitigen Märkten - N., N.

Stability in many-to-many matchings with contracts - N., N.

Preissetzungsstrategien für Neuprodukte - N., N.

Co-opetition in Two-Sided Markets - N., N.

Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Essays on Cooperation in Differential Games - Hoof, Simon

The Shanghai-Hong Kong Stock Connect: An Application of the Semi-CGARCH and Semi-EGARCH - Peitz, Christian; Feng, Yuanhua; Gilroy, Bernard Michael; Stöckmann, Nico (Asian Economic and Financial Review)

Die Niedrigzinspolitik der Europäischen Zentralbank - Gilroy, Bernard Michael; Peitz, Christian (WISU – Das Wirtschaftsstudium)

Mechanisms, Preferences, and Heterogeneity in Matching Markets - Stroh-Maraun, Nadja

Data-driven local polynomial for the trend and its derivatives in economic time series - Feng, Yuanhua; Gries, Thomas; Fritz, Marlon (Journal of Nonparametric Statistics)

Modern sector development: The role of exports and institutions in developing countries - Gries, Thomas; Grundmann, Rainer (Review of Development Economics)

Essays on the Theory of Industrial Organization: Credence Goods, Vertical Relations and Product Bundling - Heinzel, Joachim

Gender, competitiveness, and task difficulty: Evidence from the field - Hoyer, Britta; van Huizen, Thomas; Keijzer, Linda; Rezaei, Sarah; Rosenkranz, Stephanie; Westbrock, Bastian (Labour Economics)
This study examines the gender gap in competitiveness in an educational setting and tests whether this gap depends on the difficulty of the task at hand. For this purpose, we administered a series of experiments during the final exam of a university course. We confronted three cohorts of undergraduate students with a set of bonus questions and the choice between an absolute and a tournament grading scheme for these questions. To test the moderating impact of task difficulty, we (randomly) varied the difficulty of the questions between treatment groups. We find that, on average, women are significantly less likely to select the tournament scheme. However, the results show that the gender gap in tournament entry is sizable when the questions are relative easy, but much smaller and statistical insignificant when the questions are difficult.

Matching Strategies of Heterogeneous Agents under Incomplete Information in a University Clearinghouse - Hoyer, Britta; Stroh-Maraun, Nadja (Games and Economic Behavior)
We analyze the actual behavior of agents in a matching mechanism, using data from a clearinghouse at the Faculty of Business Administration and Economics at a German university, where a variant of the Boston mechanism is used. We supplement this data with data generated in a survey among the students who participated in the clearinghouse. We find that under the current mechanism over 74% of students act strategically by misrepresenting at least one of their preferences. Nevertheless, not all students are able to improve their outcome by doing so. We show that this is mainly due to the incomplete information of students and naiveté. Sophisticated students actually reach significantly better outcomes than naive students. Thus, we find evidence that naive students are exploited by sophisticated students in an incomplete information setting.

Determinants of nursing home choice: Does reported quality matter? - Schmitz, Hendrik; Stroka‐Wetsch, Magdalena A. (Health Economics)
Keywords: Health Policy

Early Disclosure of Invention and Reduced Duplication: An Empirical Test - Lück, Sonja; Balsmeier, Benjamin; Seliger, Florian; Fleming, Lee (Management Science)
Much work on innovation strategy assumes or theorizes that competition in innovation elicits duplication of research and that disclosure decreases such duplication. We validate this empirically using the American Inventors Protection Act (AIPA), three complementary identification strategies, and a new measure of blocked future patent applications. We show that AIPA—intended to reduce duplication, through default disclosure of patent applications 18 months after filing—reduced duplication in the U.S. and European patent systems. The blocking measure provides a clear and micro measure of technological competition that can be aggregated to facilitate the empirical investigation of innovation, firm strategy, and the positive and negative externalities of patenting. This paper was accepted by Joshua Gans, business strategy.
Keywords: Management Science and Operations Research; Strategy and Management

Introduction to the Special Issue “Bargaining” - Haake, Claus-Jochen; Trockel, Walter (Homo Oeconomicus)
Keywords: Industrial and Manufacturing Engineering; Environmental Engineering

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarbøe, Odvar M. (Journal of Economic Behavior & Organization)
Many countries have opened their health care markets to private for-profit providers, aiming to promote quality and choice for patients. The prices are regulated and providers compete in location and quality. We show that whereas opening a public hospital market typically raises quality, the private provider strategically locates towards the corner of the market to avoid costly quality competition. Social welfare depends on the size of the regulator's budget and on the altruism of the public provider. If the budget is large, high quality results and welfare is highest in a duopoly whenever entry is optimal. If the budget is small, quality levels in a duopoly mirror the quality level in a monopoly. It can be optimal for the regulator not to use the full budget.

Trade and economic development: global causality and development- and openness-related heterogeneity - Gries, Thomas; Redlin, Margarete (International Economics and Economic Policy)

Marktmissbrauch in digitalen Märkten - eine wettbewerbspolitische Analyse mit Fallbeispielen von Google, Facebook und Amazon - Niggemeyer, Laura

Challenges for Competition Policy in Data-Driven Mergers - Schlegel, Manuela

Marktmissbrauch in digitalen Märkten - Eine wettbewerbspolitische Analyse am Beispiel von Facebook - Neibert, Katharina

Zu den volkswirtschaftlichen Auswirkungen von Marktmacht am Fallbeispiel der Walt Disney Company - Naseri, Gitti

Preisdifferenzierung im Online-Handel am Beispiel Amazon und Obi - Laudage, Felix

Zuordnung und Anreizkompatibilität - Eine experimentelle Untersuchung - Posmetni, Lena

Auswirkungen der Preisdiskriminierung im Online Handel - Eine Wohlfahrtsanalyse am Beispiel von Amazon - Hensel, Jason

Zur Effizienzsteigerung durch Reputationsmechanismen auf digitalen Märkten - Multani, Manjinder Singh

Information asymmetry and the SEC framework in digital markets - On the role of reputation systems in alleviating buyers' skepticism and inducing their willingness to pay - Bellouchi, Houda

Zuordnungsverfahren für Tauschbörsen - N., N.

Weitsichtigkeit zur Bildung stabiler Koalitionen - eine spieltheoretische Analyse - N., N.

Verhandeltes strategisches Verhalten - N., N.

Kronzeugenprogramme zur Aufdeckung von Kartellen - Eine spieltheoretische Analyse - N., N.

Eine ökonomische Analyse der Piraterie in zweiseitigen Softwaremärkten - N., N.

Kulturelle Unterschiede beim Lösen von Verhandlungsproblemen - N., N.

Productivity optimization through project matching - N., N.

Matching Mechanisms and Organ Exchange - N., N.

Cartel Fines in the European Union - N., N.

Anspruchsregeln in Verhandlungen - N., N.

Die Zusammenstellung eines Sortiments als Beispiel interdependenter Verhandlungen - N., N.

Matching in Netzwerken - N., N.

Prudence and prevention: Empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik
Theoretical papers show that optimal prevention decisions in the sense of selfprotection (i.e., primary prevention) depend not only on the level of (second-order) risk aversion but also on higher-order risk preferences such as prudence (third-order risk aversion). We study empirically whether these theoretical results hold and whether prudent individuals show less preventive (self-protection) effort than non-prudent individuals. We use a unique dataset that combines data on higher-order risk preferences and various measures of observed real-world prevention behavior. We find that prudent individuals indeed invest less in self-protection as measured by influenza vaccination. This result is driven by high risk individuals such as individuals >60 years of age or chronically ill. We do not find a clear empirical relationship between riskpreferences and prevention in the sense of self-insurance (i.e. secondary prevention). Neither risk aversion nor prudence is related to cancer screenings such as mammograms, Pap smears or X-rays of the lung.
Keywords: prudence; risk preferences; prevention; vaccination; screening

Economic Retirement Age and Lifelong Learning - a theoretical model with heterogeneous labor and biased technical change - Gries, Thomas; Jungblut, Stefan; Krieger, Tim; Meyer, Henning (German Economic Review)

Price competition and the Bertrand model: The paradox of the German mobile discount market - Kaimann, Daniel; Hoyer, Britta (Applied Economics Letters)
We investigate the degree of price competition among telecommunication firms. Underlying a Bertrand model of price competition, we empirically model pricing behaviour in an oligopoly. We analyse panel data of individual pricing information of mobile phone contracts offered between 2011 and 2017. We provide empirical evidence that price differences as well as reputational effects serve as a signal to buyers and significantly affect market demand. Additionally, we find that brands lead to an increase in demand and thus are able to generate spillover effects even after price increase.

The Common Enemy Effect under Strategic Network Formation and Disruption - Hoyer, Britta; Haller, Hans (Journal of Economic Behavior & Organization)
Social psychology studies the "common enemy effect", the phenomenon that members of a group work together when they face an opponent, although they otherwise have little in common. An interesting scenario is the formation of an information network where group members individually sponsor costly links. Suppose that ceteris paribus, an outsider appears who aims to disrupt the information flow within the network by deleting some of the links. The question is how the group responds to this common enemy. We address this question for the homogeneous connections model of strategic network formation, with two-way flow of information and without information decay. For sufficiently low linkage costs, the external threat can lead to a more connected network, a positive common enemy effect. For very high but not prohibitively high linkage costs, the equilibrium network can be minimally connected and efficient in the absence of the external threat whereas it is always empty and ineffi cient in the presence of the external threat, a negative common enemy effect. For intermediate linkage costs, both connected networks and the empty network are Nash for certain cost ranges.

Network Formation and Disruption - An Experiment: Are equilibrium networks too complex? - Endres, Angelika Elfriede; Recker, Sonja; Mir Djawadi, Behnud; Hoyer, Britta (Journal of Economic Behavior and Organization)
Models on network formation have often been extended to include the potential of network disruption in recent years. Whereas the theoretical research on network formation under the threat of disruption has thus gained prominence, hardly any experimental research exists so far. In this paper, we therefore experimentally study the emergence of networks including the aspect of a known external threat by relating theoretical predictions by Dzuibiński and Goyal (2013) to actual observed behaviour. We deal with the question if subjects in the role of a strategic Designer are able to form safe networks for least costs while facing a strategic Adversary who is going to attack their networks. Varying the costs for protecting nodes, we designed and tested two treatments with different predictions for the equilibrium network and investigated whether one of the least cost equilibrium networks was more likely to be reached. Furthermore, the influence of the subjects’ farsightedness on their decision-making process was elicited and analysed. We find that while subjects are able to build safe networks in both treatments, equilibrium networks are only built in one of the two treatments. In the other treatment, predominantly safe networks are built but they are not for least costs. Additionally, we find that farsightedness –as measured in our experiment– has no influence on whether subjects are able to build safe or least cost equilibrium networks. Two robustness settings with a reduced external threat or more liberties to modify the initial networks qualitatively confirm our results. Overall, in this experiment observed behaviour is only partially in line with the theoretical predictions by Dzuibiński and Goyal (2013).

Credence Goods Markets with Heterogeneous Experts - Heinzel, Joachim Maria Josef
In this paper, we analyze a credence goods model adjusted to the health care market with regulated prices and heterogeneous experts. Experts are physicians and are assumed to differ in their cost of treating a small problem. We investigate the effects of this heterogeneity on the physicians’ level of fraud and on the patients’ search for second opinions. We find that introducing a fraction of more efficient low-cost physicians always increases social welfare, but in some cases only because of the raised physicians’ surplus. When the low-cost physicians’ cost advantage is small, imposing a share of low-cost physicians does not change the equilibrium fraud level. When the cost advantage is large, however, different changes in the fraud level occur depending on the share of generated low-cost physicians, the search rate and the initial level of fraud.
Keywords: credence goods; treatment efficiency; heterogeneous experts; overcharging

Credence Goods Markets with Fair and Opportunistic Experts - Heinzel, Joachim Maria Josef
We analyze a credence goods market adapted to a health care market with regulated prices, where physicians are heterogeneous regarding their fairness concerns. The opportunistic physicians only consider monetary incentives while the fair physicians, in addition to a monetary payoff, gain an non-monetary utility from being honest towards patients. We investigate how this heterogeneity affects the physicians’ equilibrium level of overcharging and the patients’ search for second opinions (which determines overall welfare). The impact of the heterogeneity on the fraud level is ambiguous and depends on several factors such as the size of the fairness utility, the share of fair physicians, the search level and the initial fraud level. Introducing heterogeneity does not affect the fraud or the search level when the share of fair physicians is small. However, when social welfare is not at its maximum, social welfare always increases if we introduce a sufficiently large share of fair physicians.
Keywords: credence goods; heterogeneous experts; fairness; overcharging

Secular stagnation? Is there statistical evidence of an unprecedented, systematic decline in growth? - Fritz, Marlon; Gries, Thomas; Feng, Yuanhua (Economics Letters)

Growth Trends and Systematic Patterns of Boom and Busts –Testing 200 Years of Business Cycle Dynamics - Gries, Thomas; Fritz, Marlon; Yuanhua, Feng (Oxford Bulletin of Economics and Statistics)

New Dimensions of Service Offshoring in World Trade - Atkins, Marc; Gilroy, Bernard Michael; Seiler, Volker (Intereconomics)

The Impact of Monetary Policy on Investment Bank Profitability in Unequal Economies - Gilroy, Bernard Michael; Golderbein, Alexander; Peitz, Christian; Stöckmann, Nico (Operations Research Proceedings 2018)

Social-Trading und Copy-Trading - Krimphove, Dieter; Peitz, Christian (Fintechs: Rechtliche Grundlagen moderner Finanztechnologien)

The Decomposability of the Nash Bargaining Solution in Labor Markets - Haake, Claus-Jochen; Upmann, Thorsten; Duman, Papatya
In this paper, we analyze the two-dimensional Nash bargaining solution (NBS) deploying a standard labor market negotiations model (see McDonald and Solow, 1981; Creedy and McDonald, 1991). We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems such that the (Cartesian) product of the solutions of these problems replicates the solution of the two-dimensional problem, if the NBS is applied. However, this decomposition fails for any solution concept that does not satisfy the axiom of Independence of Irrelevant Alternatives (IIA axiom). Our decomposition result has significant implications for actual negotiations, as it allows for the decomposition of a multi-issue bargaining problem into a set of simpler problems, in particular a set of single-issue bargaining problems. In this way, the decomposition may help facilitate negotiations in labor markets and also in other environments.
Keywords: Labor market negotiations; Efficient bargains; Nash bargaining solution; Sequential bargaining; Restricted bargaining games

Duality for General TU-games Redefined - Aslan, Fatma; Duman, Papatya; Trockel, Walter
We criticize some conceptual weaknesses in the recent literature on coalitional TUgames and propose, based on our critics, a new definition of dual TU-games that coincides with the one in the literature on the class of super-additive games. We justify our new definition in four alternative ways: 1. Via an adequate definition of ecient payo vectors. 2. Via a modification of the Bondareva-Shapley duality. 3. Via an explicit consideration of \coalition building". 4. Via associating general TU-games to coalition-production economies. Rather than imputations, we base our analysis on a modification of aspirations.
Keywords: TU-games; duality; core; c-Core; cohesive games; complete game efficiency

Evolutionary equilibrium in contests with stochastic participation: Entry, effort and overdissipation - Gu, Yiquan; Hehenkamp, Burkhard; Leininger, Wolfgang (Journal of Economic Behavior & Organization)
This paper examines the evolutionary stability of behaviour in contests where players’ participation can be stochastic. We find, for exogenously given participation probabilities, players exert more effort under the concept of a finite-population evolutionarily stable strategy (FPESS) than under Nash equilibrium (NE). We show that there is ex-ante overdissipation under FPESS for sufficiently large participation probabilities, if, and only if, the impact function is convex. With costly endogenous entry, players enter the contest with a higher probability and exert more effort under FPESS than under NE. Importantly, under endogenous entry, overdissipation can occur for all (Tullock) contest success functions, in particular those with concave impact functions.

A New Theory of Demand-Restricted Growth: The Basic Idea - Gries, Thomas (The American Economist)

Bundling in a Distribution Channel with Retail Competition - Heinzel, Joachim Maria Josef
We analyze the incentives for retail bundling and the welfare effects of retail bundling in a decentralized distribution channel with two retailers and two monopolistic manufacturers. One manufacturer exclusively sells his good to one retailer, whereas the other manufacturer sells his good to both retailers. Thus, one retailer is a monopolist for one product but competes with the other retailer in the second product market. The two-product retailer has the option to bundle his goods or to sell them separately. We find that bundling aggravates the double marginalization problem for the bundling retailer. Nevertheless, when the retailers compete in prices, bundling can be more profitable than separate selling for the retailer as bundling softens the retail competition. The ultimate outcome depends on the manufacturers’ marginal costs. Given retail quantity competition, however, bundling is in no case the retailer’s best strategy. Furthermore, we show that profitable bundling reduces consumer and producer surplus in the equilibrium.
Keywords: retail bundling; leverage theory; double marginalization

The Role of Prices Relative to Supplemental Benefits and Service Quality in Health Plan Choice - Bünnings, Christian; Schmitz, Hendrik; Tauchmann, Harald; Ziebarth, Nicolas R. (Journal of Risk and Insurance)

Pirates – The Young and the Jobless: The Effect of Youth Bulges and Youth Labor Market Integration on Maritime Piracy - Gries, Thomas; Redlin, Margarete (Defence and Peace Economics)

"Data-Driven Mergers" in digitalen Märkten - eine wettbewerbspolitische Analyse - Lütkevedder, Dennis

On the Implications of Big Data for Competition Policy - Big data, Market power, Competition law - Memon, Uzair Ahmed

Risiken und Gefahren von Marktmacht in digitalen Märkten - eine wettbewerbspolitische Analyse - Milczarek, André

Digitale Märkte - Zu den Auswirkungen von Big Data auf Marktmacht und die Bildung von Kartellen - Heinrichs, Fabian

Anreizwirkungen der Bonusregelung - Eine wettbewerbspolitische Analyse - Fortmeier, Julia

The intersection of privacy and competition law - Lessons from data-driven mergers - Hagedorn, Carolin

Die Akquisition von Double Click durch Google - eine wettbewerbspolitische Analyse - Ayyildiz, Berfin

Merger Analysis in Data-Driven Markets - An Economic Policy Perspective - Shelepova, Ekaterina

Marktmacht in digitalen Märkten - Shanmugaratnam, Suganya

The Effectiveness of Leniency Programs and Whistleblowing in Discouraging Cartel Activities - Faizan, Ahmed

Intermediaries in Networks - N., N.

Logrolling-Prozess: Theorie und formale Darstellung einer verhandlungsunterstützenden Methode - N., N.

Stability in two-sided matchings with asymmetric information - N., N.

Sincere and Sophisticated Players in Matching Markets - N., N.

Mechanismen zur Informationsgewinnung in Verhandlungen - N., N.

Die faire Verteilung unteilbarer Güter - N., N.

Axiomatisierungen des Banzhaf-Wertes - N., N.

Compatibilities in Matching Mechanisms - N., N.

Faire Aufteilung von unteilbaren Gütern: Untersuchung von Algorithmen auf Effizienz und Neidfreiheit - N., N.

Anwendung und Vergleich von Verhandlungslösungen auf das Netzwerk-Design-Problem - N., N.

Verhandlungen mit Intermediären in IT-Märkten: eine spieltheoretische Analyse - N., N.